Lattice Paths, Sampling Without Replacement, and Limiting Distributions - Kuba, M.; Panholzer, A.; Prodinger, H. (The Electronic Journal of Combinatorics, 2009)
In this work we consider weighted lattice paths in the quarter plane ${\Bbb N}_0×{\Bbb N}_0$. The steps are given by $(m,n)→(m-1,n)$, $(m,n)→(m,n-1)$ and are weighted as follows: $(m,n)→(m-1,n)$ by $m/(m+n)$ and step $(m,n)→(m,n-1)$ by $n/(m+n)$. The considered lattice paths are absorbed at lines $y=x/t -s/t$ with $t\in{\Bbb N}$ and $s\in{\Bbb N}_0$. We provide explicit formulæ for the sum of the weights of paths, starting at $(m,n)$, which are absorbed at a certain height $k$ at lines $y=x/t -s/t$ with $t\in{\Bbb N}$ and $s\in{\Bbb N}_0$, using a generating functions approach. Furthermore these weighted lattice paths can be interpreted as probability distributions arising in the context of Pólya-Eggenberger urn models, more precisely, the lattice paths are sample paths of the well known sampling without replacement urn. We provide limiting distribution results for the underlying random variable, obtaining a total of five phase changes.